Identification of Mutations Conferring Tryptanthrin Resistance to Mycobacterium smegmatis - Svetlana G. Frolova; Ksenia M. Klimina; Ravinder Kumar; Aleksey A. Vatlin; Deepak B. Salunke; Pravin Kendrekar; Valery N. Danilenko; Dmitry A. Maslov (MDPI AG, 2020)
Tuberculosis (TB), caused by Mycobacterium tuberculosis, is a global burden, responsible for over 1 million deaths annually. The emergence and spread of drug-resistant M. tuberculosis strains (MDR-, XDR- and TDR-TB) is the main challenge in global TB-control, requiring the development of novel drugs acting on new biotargets, thus able to overcome the drug-resistance. Tryptanthrin is a natural alkaloid, with great therapeutic potential due to its simple way of synthesis and wide spectrum of biological activities including high bactericidal activity on both drug-susceptible and MDR M. tuberculosis strains. InhA was suggested as the target of tryptanthrins by in silico modeling, making it a promising alternative to isoniazid, able to overcome drug resistance provided by katG mutations. However, neither the mechanism of action of tryptanthrin nor the mechanism of resistance to tryptanthrins was ever confirmed in vitro. We show that the MmpS5-MmpL5 efflux system is able to provide resistance to tryptanthrins using an in-house test-system. Comparative genomic analysis of spontaneous tryptanthrin-resistant M. smegmatis mutants showed that mutations in MSMEG_1963 (EmbR transcriptional regulator) lead to a high-level resistance, while those in MSMEG_5597 (TetR transcriptional regulator) to a low-level one. Mutations in an MFS transporter gene (MSMEG_4427) were also observed, which might be involved in providing a basal level of tryptanthrins-resistance.